Original paperConservative strategy in patients with ST-segment elevation myocardial infarction - Zalewski, Jarosław; Nycz, Krzysztof; Przewłocki, Tadeusz; Durak, Monika; Andres, Marek; Lech, Piotr; Pieniążek, Piotr; Żmudka, Krzysztof (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2010)
Background : Clinical outcomes of patients with ST-segment elevation myocardial infarction (STEMI) disqualified from an invasive strategy (InvS) are poorly understood. Aim : To investigate the short-term result of a conservative strategy (ConS) in a real-life population of patients with STEMI. Material and methods : 1031 patients with STEMI were retrospectively analyzed. Of these, 194 (18.8%) patients were initially qualified to the ConS. For the remaining 837 (81.2%) patients the InvS was applied. Results : The most frequent reasons for disqualification from an InvS in STEMI patients were the duration of ischemia > 12 h (81.4%), aborted STEMI (9.8%) and anticipated transportation time > 2 h (3.1%). On admission, in the group of InvS, cardiogenic shock was noted in 45 (5.4%) patients. Death within 30 days was more frequently observed in STEMI patients who underwent ConS vs. InvS (13.9% vs. 9.0%, p = 0.037). During initial hospitalization 22 (11.3%) patients who underwent ConS and 34 (4.1%, p < 0.001) with InvS developed symptoms of heart failure (Killip class 2-4). Age (OR 1.07 per year, 95% CI 1.04-1.11, p < 0.0001) and conservative strategy (OR 1.55, 95% CI 0.73-4.86, p = 0.035) were the independent predictors of death within 30 days. Moreover, in patients with InvS cardiogenic shock on admission (OR 52.4, 95% CI 18.7-134.1, p < 0.0001) and in patients with ConS heart failure during hospitalization (OR 10.8, 95% CI 3.2-36.7, p = 0.0002) independently influenced the 30-day mortality (c-statistics 0.83). Conclusions : Duration of ischemia of more than 12 h was the main reason for disqualification from InvS. Applied ConS was associated with higher 30-day mortality when compared to InvS. The symptoms of heart failure were an independent predictor of death within 30 days in patients with ConS.